MicroRNA-21 Mediates a Positive Feedback on Angiotensin II-Induced Myofibroblast Transformation - Li D; Mao C; Zhou E; You J; Gao E; Han Z; Fan Y; He Q; Wang C (Dove Medical Press, 2020)
Dongjiu Li,1,* Chengyu Mao,1,* En Zhou,1,* Jiayin You,2,* Erhe Gao,3 Zhihua Han,1 Yuqi Fan,1 Qing He,1 Changqian Wang1 1Department of Cardiology, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai 200011, People’s Republic of China; 2Department of Emergency, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai 200011, People’s Republic of China; 3Center for Translational Medicine, Department of Pharmacology, Lewis Katz School of Medicine, Temple University, Philadelphia, PA, USA*These authors contributed equally to this workCorrespondence: Changqian Wang Email wangcqdr17@163.comObjective: Post myocardial infarction (MI) fibrosis has been identified as an important factor in the progression of heart failure. Previous studies have revealed that microRNA-21 (miR-21) plays an important role in the pathogenesis of fibrosis. The purpose of this study was to explore the role of miR-21 in post-MI cardiac fibrosis.Material and Methods: MI was established in wild-type (WT) and miR-21 knockout (KO) mice. Primary mice cardiac fibroblasts (CFs) were isolated from WT and miR-21 KO mice and were treated with angiotensin II (Ang II) or Sprouty1 (Spry1) siRNA. Histological analysis and echocardiography were used to determine the extent of fibrosis and cardiac function.Results: Compared with WT mice, miR-21 KO mice displayed smaller fibrotic areas and decreased expression of fibrotic markers and inflammatory cytokines. In parallel, Ang II-induced myofibroblasts transformation was partially inhibited upon miR-21 KO in primary CFs. Mechanistically, we found that the expression of Spry1, a previously reported target of miR-21, was markedly increased in miR-21 KO mice post MI, further inhibiting ERK1/2 activation. In vitro studies showed that Ang II activated ERK1/2/TGF-β/Smad2/3 pathway. Phosphorylated Smad2/3 further enhanced the expression of α-SMA and FAP and may promote the maturation of miR-21, thereby downregulating Spry1. Additionally, these effects of miR-21 KO on fibrosis were reversed by siRNA-mediated knockdown of Spry1.Conclusion: Our findings suggest that miR-21 promotes post-MI fibrosis by targeting Spry1. Furthermore, it mediates a positive feedback on Ang II, thereby inducing the ERK/TGF-β/Smad pathway. Therefore, targeting the miR-21–Spry1 axis may be a promising therapeutic option for ameliorating post-MI cardiac fibrosis.Keywords: cardiac fibrosis, myocardial infarction, microRNA-21, Sprouty1, ERK/TGF-β/Smad signaling pathway